A brief survey of preparation and heat transfer enhancement of hybrid nanofluids - Hussien, Ahmad A. (Strojniški vestnik, 2019)
The investigation of the domestic application of heat flux dissemination is in high demand. The best strategy to obtain a coolant with an ideal execution is by including particular sorts of nanoparticles in the base fluid. The utilization of nanofluids escalates the heat transfer coefficient through the enhancement of the base fluid%s thermal conductivity. An advanced coolant (hybrid nanofluid) was delivered by blending two or more different types of nano-sized particles with conventional fluid. This article mainly aims to cover the recent publications on hybrid nanofluids on different aspects, such as preparation, thermophysical properties, and heat transfer enhancement. In general, the combination of different nanoparticle properties results in excellent thermal conductivity: improvement in heat transfer coefficient was up to 148 % compared to the base fluid. Moreover, a moderate increase on pressure drop has been detected due to the presence of composite nanoparticles. In any case, the anticipated results for both thermal conductivity and viscosity values utilizing conventional relationships were distinctive from the experimental results.
Keywords: hibridni nanofluidi; hybrid nanofluids; Nusselt number; Nusseltovo število; thermal applications; thermal conductivity; toplotna prestopnost; toplotna prevodnost; toplotne aplikacije; viscosity; viskoznost